Discontinuous negation in Hausa - Crysmann, Berthold (Proceedings of the 17th International Conference on Head-Driven Phrase Structure Grammar, 2010)
Investigating the morphological and syntactic properties of discontinuous negative marking in Hausa,I shall suggest a constructional approach involving edge inflection, accounting simultaneously forthe morphologically bound nature of the initial marker and its interaction with the TAM system,haplology of the final marker, and wide scope over coordination. I will argue that the degree ofmorphological integration of initial markers and haplology of final markers both favour an edgefeature approach over phrasal affixation.